Two new syncephalous species of Eremanthus (Asteraceae: Vernonieae) from southeastern Brazil - Loeuille, Benoit; Pirani, José Rubens (Phytotaxa, 2016)
Eremanthus praetermissus and E. ovatifolius, two new species from Brazil, are here described and illustrated. Eremanthus praetermissus is endemic to Serra do Mar, in the northeastern part of São Paulo state and the southern part of Rio de Janeiro state; it is characterized by hemispherical, brown syncephalia, heads connate for 1/3 to 2/5 of their length, with 3–4 florets per head and brown phyllaries with purple apices. Eremanthus ovatifolius is endemic to campos rupestres of Pico da Aliança, in the eastern part of Minas Gerais state, and is characterized by ovate leaves, hemispherical syncephalia, heads connate for 1/4 to 1/2 of their length and 3–4 florets per head. The affinities of these species are discussed. A key to all species of Eremanthus is provided.